An Exploration of Analgesia Options for Australian Sheep - Shari Cohen; Emily Foss; Thierry Beths; Gabrielle C. Musk (Animals, 2024)
During their lifetime, sheep undergo many painful husbandry and disease processes. Procedures undertaken on the farm, such as tail docking, castration, and mulesing, all cause considerable pain. In addition, sheep may experience painful diseases and injuries that require treatment by veterinary practitioners, and in biomedical research, sheep may undergo painful experimental procedures or conditions. It is important due to ethics, animal welfare, social licence, and, at times, legal requirements for farmers, veterinary practitioners, and researchers to provide pain relief for animals in their care. While there is a heightened awareness of and a greater interest in animal welfare, there remain few licensed and known analgesia options for sheep within Australia. A literature review was undertaken to identify currently known and potential future options for analgesic agents in sheep in farm and biomedical settings. Non-steroidal anti-inflammatories, opioids, local anaesthetics, α2 adrenoreceptor agonists, and NMDA receptor antagonists are some of the more common classes of analgesic drugs referred to in the literature, but few drugs are registered for use in sheep, with even fewer proven to be effective. Only six analgesic product formulations, namely, lignocaine (e.g., Numocaine®), Tri-Solfen®, ketamine, xylazine, and meloxicam (oral transmucosal and injectable formulations), are currently registered in Australia and known to be efficacious in some types of painful conditions in sheep. The gap in knowledge and availability of analgesia in sheep can pose risks to animal welfare, social licence, and research outcomes. This article presents a summary of analgesic agents that have been used in sheep on farms and in clinical veterinary and biomedical research settings along with details on whether their efficacy was assessed, doses, routes of administration, indication for use, and pain assessment techniques (if any) used. The outcome of this research highlights the challenges, gaps, and opportunities for better analgesia options in sheep.